2013
DOI: 10.1016/j.cropro.2013.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Fungal species isolated from peanuts in major Kenyan markets: Emphasis on Aspergillus section Flavi

Abstract: A survey was conducted in Nairobi, Nyanza and Western provinces in Kenya between March and July 2009 with 1263 peanut products sampled out of which 705 samples underwent microbial analysis. The study aimed at determining the incidence of fungal species e emphasis on Aspergillus section Flavi e associated with peanut products. A 0.5 kg representative sample was obtained from each surveyed vendor and the colony forming units (CFU) of fungal species determined. The samples were also analyzed for total aflatoxin l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 54 publications
(82 reference statements)
0
20
1
Order By: Relevance
“…Previous studies have reported isolation of diverse fungal pathogens from peanuts in Kenya (Mutegi et al 2012;Wagacha et al, 2013). Although A. flavus and A. parasiticus are the species most frequently implicated in aflatoxin contamination (Cotty, 2006), the wide fungal species diversity poses a health risk of exposing peanut consumers to other secondary metabolites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported isolation of diverse fungal pathogens from peanuts in Kenya (Mutegi et al 2012;Wagacha et al, 2013). Although A. flavus and A. parasiticus are the species most frequently implicated in aflatoxin contamination (Cotty, 2006), the wide fungal species diversity poses a health risk of exposing peanut consumers to other secondary metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Peanuts in Kenya are frequently infected by A. flavus and A. parasiticus (Mutegi, Ngugi, Hendriks, & Jones, 2012;Wagacha, Mutegi, Karanja, Kimani, & Christie, 2013) and this infection can occur at all stages in the peanut value chain (Waliyar et al, 2005). Determination of the level of fungal infection of a foodstuff as well as establishing the occurrence of common species is important as the fungal population and diversity could give an indication of the food quality and the presence and types of mycotoxins (Suanthie, Cousin, & Woloshuk, 2009).…”
mentioning
confidence: 99%
“…These findings do not resonate provisions by Wagacha et al (2013). According to Wagacha et al (2013), the incidence and population of A. flavus S-strain significantly and positively correlate with the levels of total aflatoxin in groundnuts. This may be due to sample size.…”
Section: Population Of Aspergillus Species and Aflatoxin Contaminatiomentioning
confidence: 44%
“…High aflatoxin contamination levels (above the 10 ppb limit set by KEBS) have also been reported in raw and processed groundnuts from different regions in Kenya (Gachomo et al, 2004;Mutegi et al, 2012Mutegi et al, , 2013Wagacha et al, 2013). In a recent study Mutegi et al (2012), 37% of groundnuts including products like groundnut butter and groundnut flour sampled from Nairobi, Nyanza and Western Kenya failed to meet the 10 ppb total aflatoxin limit set by the Kenya Bureau of Standards (KEBS, 2007).…”
Section: Population Of Aspergillus Species and Aflatoxin Contaminatiomentioning
confidence: 99%
“…Several researchers have investigated peanuts for the presence of Aflatoxins, particularly AFB1 (Bankole et al, 2005;Barro et al, 2002;Mutegi et al, 2009). Iqbal et al (2013) reported the level of AFB1 ranging from 2.4 to 12.3 µg/kg but Wagacha et al (2013) reported AFB1 level in peanut products ranging from 0 to 1629 µg/kg. Therefore, our study is in agreement with other previous studies in other countries on the natural occurrence of AFB1 in peanut samples.…”
Section: Resultsmentioning
confidence: 99%